Does Size Matter? Comparing Medium‐Term Cost‐Effectiveness of Group Homes with Institutional Care in South Korea. Issue 2 (15th June 2016) - Nho, Choong Rai; Woo, Seokjin; Kang, Hyunah; Chun, JongSerl; Chung, Ick‐Joong
Abstract : Using unique 5‐year longitudinal data on Korean children in group homes and those under institutional care, this paper compared the medium‐term cost‐effectiveness of group homes and that of institutional care facilities in terms of developmental outcomes. Results from propensity score matching estimation show that children in group homes tend to have more desirable positive outcomes and fewer behavioral problems in the medium term to a statistically significant margin. The cost‐effectiveness ratio of being placed in a group home is consistently higher than placement in an institutional care facility. That is, for one dollar spent on an out‐of‐home care service, we anticipate the children in group homes have more desirable outcomes in the medium term than their counterparts in institutional care facilities.